Detection of low frequency artemisinin resistance mutations, C469Y, P553L and A675V, and fixed antifolate resistance mutations in asymptomatic primary school children in Kenya - Victor Osoti; Kevin Wamae; Leonard Ndwiga; Paul M. Gichuki; Collins Okoyo; Stella Kepha; Kibor Keitany; Regina Kandie; Stephen Aricha; Rosebella Kiplagat; Charles Mwandawiro; Philip Bejon; et al. (BMC Infectious Diseases)
Abstract Background To understand the emergence and spread of drug-resistant parasites in malaria-endemic areas, accurate assessment and monitoring of antimalarial drug resistance markers is critical. Recent advances in next-generation sequencing (NGS) technologies have enabled the tracking of drug-resistant malaria parasites. Methods In this study, we used Targeted Amplicon Deep Sequencing (TADS) to characterise the genetic diversity of the Pfk13, Pfdhfr, Pfdhps, and Pfmdr1 genes among primary school-going children in 15 counties in Kenya (Bungoma, Busia, Homa Bay, Migori, Kakamega, Kilifi, Kirinyaga, Kisii, Kisumu, Kwale, Siaya, Tana River, Turkana, Vihiga and West Pokot). A total of 920 dried blood spot (DBS) samples collected from 121 selected primary schools within the country were used to extract genomic DNA. A nested polymerase chain reaction (PCR) was used to generate amplicons that were sequenced to determine the prevalence of known and novel polymorphisms. Results Pfk13 mutations associated with artemisinin resistance were present as mixed genotype infections for the C469Y mutation in 23 samples (4%), the A675V mutation in 2 samples (1.7%), and the P553L mutation in 7 samples (1.2%). The A578S mutation, was also identified in mixed infections, appearing in 15.2% of the 87 samples analysed. The Pfdhfr 51I and 108 N pyrimethamine-resistance mutations were at fixation (100% frequency), and the Pfmdr1 Y184F mutation, which is linked to reduced susceptibility to several antimalarial drugs, especially those used in combination therapies for malaria treatment, was detected in 97.5% of the samples as mixed-genotype infections. Conclusion The genomic surveillance of asymptomatic school children in Kenya provides an early warning signal of at least 1 of the 3 validated artemisinin resistance mutations circulating in all regions in Western Kenya sampled except Homa Bay and Kisii Counties. These signals in asymptomatic and mixed infections would have been missed without deep sequencing.